PENGARUH PEMBERIAN PROBIOTIK DARI MIKROBA LOKAL TERHADAP TEBAL KERABANG, PENURUNAN BERAT, DAN NILAI HAUGH UNIT TELUR YANG DISIMPAN SEPULUH HARI - Jenny Marthika Sari; Tintin Kurtini; Madi Hartono (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
This study was conducted to 1) determine the effect local of probiotic supplements on shell thickness, weight loss persentage, and Haugh unit of eggs which stored ten days; 2) determine the optimal  level of supplements local of probiotic on shell thickness, weight loss presentage, and Haugh unit of eggs which stored ten days. This research was held on 08--19 December 2014  in the CV. Varia Agung Jaya henhouse laying  in  the District of  Seputih Mataram, Center of Lampung  Regency and continued on 20 December 2014--18 January 2015 in the Laboratory of Microbiology, Laboratory of Molecular Biology Faculty, University of Lampung. The study used completely randomized design (CRD) with 4 treatments of  local  probiotics in the diet (0%, 1%, 2%, and 3%) and 5 replications. Data obtained was analyzed using analysis of variance at 5% level and continued Orthogonal Polynomial test at 5% level. Based on these results we can conclude: effect of local probiotics in the diet (0,1,2, and 3%) no significant (P> 0.05) on the weight loss presentage and  Haugh unit of eggs which stored ten days, but significant (P <0.05) on  shell thickness. Increasing the percentage of local probiotic on the ration will improve shell thickness indicated by the regression equation ŷ = 0.42 + 0,24x, with r = 0.68 and R2 = 0.47. (Keywords: Local of  probiotic, Shell thickness, Weight loss, and  Haugh unit).